2010
DOI: 10.1371/journal.ppat.1001061
|View full text |Cite
|
Sign up to set email alerts
|

Variations in TcdB Activity and the Hypervirulence of Emerging Strains of Clostridium difficile

Abstract: Hypervirulent strains of Clostridium difficile have emerged over the past decade, increasing the morbidity and mortality of patients infected by this opportunistic pathogen. Recent work suggested the major C. difficile virulence factor, TcdB, from hypervirulent strains (TcdBHV) was more cytotoxic in vitro than TcdB from historical strains (TcdBHIST). The current study investigated the in vivo impact of altered TcdB tropism, and the underlying mechanism responsible for the differences in activity between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
143
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(152 citation statements)
references
References 50 publications
(69 reference statements)
8
143
1
Order By: Relevance
“…It was reported that TcdA is relatively well conserved, while TcdB has much variability, 38,39 especially the RBD region. 38 The N terminus encompassing the GTD and CPD domains is more conserved between historical and epidemic strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that TcdA is relatively well conserved, while TcdB has much variability, 38,39 especially the RBD region. 38 The N terminus encompassing the GTD and CPD domains is more conserved between historical and epidemic strains.…”
Section: Discussionmentioning
confidence: 99%
“…38 The N terminus encompassing the GTD and CPD domains is more conserved between historical and epidemic strains. In our previous study 37 and consistent with others, 35,36 we indicated that the N-terminus of TcdB was able to elicit a protective antibody response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH-induced conformational changes of TcdB were assessed as described previously (34). Assay plates were read in Spectramax M5 plate reader (Molecular Devices).…”
Section: Methodsmentioning
confidence: 99%
“…These include genetic divergence from other strains that enhances cell tropism, mutation in the tcdC gene that may result in a removal of logphase repression of toxin expression, and increased sporulation. [14][15][16] Finally, NAP-1/027 and other hypervirulent strains have high-level resistance to fluoroquinolones. 10 Currently, this strain accounts for more than 35% of all strains recovered from patients with CDIs.…”
mentioning
confidence: 99%